162 The association of two rare neurological diseases: a multicentre study of 16 patients with AChR antibody myasthenia gravis and AQP4 antibody neuromyelitis optica spectrum disorder. Issue 3 (9th February 2012) - Leite, M I; Coutinho, E; Callegaro, D; Lana-Peixoto, M; Waters, P; Sato, D; Melamud, L; Graham, A; Vincent, A; Palace, J
Abstract : Aquaporin-4 antibody-mediated neuromyelitis optica spectrum disorders (AQP4-NMOSD) and acetylcholine receptor antibody-mediated myasthenia gravis (AChR-MG) are rare neurological autoimmune diseases. We describe the largest cohort of patients with both conditions. The clinical features and sequential antibody levels of AChR and AQP4 are described in patients collated from the UK, Brazil, Portugal, Japan and Argentina. Fifteen of the 16 patients were female. All had early-onset MG (median onset age: 26.5 years) and 11/13 with generalised MG were thymectomised (none had thymomas). The MG was mild or moderate, and in 13 patients, immunosuppression was either not given or was eventually withdrawn. The MG preceded NMOSD in 14 patients by 11.5 years. In 4/5 patients with serial samples, AQP4 Abs were detectable up to 16 years prior to NMOSD onset, with two having AQP4 Abs prior to thymectomy. Of the two patients that presented first with NMOSD, one had AChR Abs 6 years prior to MG onset. These diseases were found to coexist 50 times more frequently than expected by chance suggesting a common autoimmunisation process. This report highlights the need to perform tests to look for AQP4-NMOSD in patients with AChR-MG that show features of optic nerve or central nervous system involvement such as demyelinating disease.